2015
DOI: 10.1097/qai.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Assessment, Counseling, and Support Interventions to Improve Health-Related Outcomes in People Living With HIV/AIDS

Abstract: Background While numerous studies have shown that severe to moderate wasting at the time of antiretroviral therapy (ART) initiation is strongly predictive of mortality, it remains unclear whether nutritional interventions at or prior to ART initiation will improve outcomes. This review examines data on nutrition assessment, counseling, and support (NACS) interventions in resource-limited settings. Methods We identified articles published between 2005 and 2014 on the effectiveness of NACS interventions, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 32 publications
2
38
0
4
Order By: Relevance
“…Research has indicated that locally and culturally sound nutritional counselling is vital to enhance and maintain the nutritional status of people living with HIV [42][43][44]. Engaging with participants and empowering them to take control of their nutrition and health is the fundamental principle of successful nutritional counselling in HIV care settings [14]. Evidence from other studies suggests that standard nutritional counselling should empower individuals with essential nutritional knowledge and assist them to understand the importance of nutrition to make informed decisions regarding their nutritional options [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that locally and culturally sound nutritional counselling is vital to enhance and maintain the nutritional status of people living with HIV [42][43][44]. Engaging with participants and empowering them to take control of their nutrition and health is the fundamental principle of successful nutritional counselling in HIV care settings [14]. Evidence from other studies suggests that standard nutritional counselling should empower individuals with essential nutritional knowledge and assist them to understand the importance of nutrition to make informed decisions regarding their nutritional options [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…To address HIV-related undernutrition and to improve HIV care outcomes, nutritional programs have been incorporated into HIV care services in many countries, particularly in sub-Saharan Africa [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that for some patients, HIV has become the central or perhaps the only health issue that they felt needed regular management. Exercise does not directly influence immunological or virological outcomes in PLWH (O’Brien, Tynan, Nixon, & Glazier, 2016) and the role of diet on these outcomes is mixed (Tang, Quick, Chung, & Wanke, 2015). Furthermore, our data suggest that some PLWH prioritize behaviors that improve HIV-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is often difficult to maintain an adherent behavior for a long time. Counseling is a strategy applied in different contexts and environments to empower the patient into making decisions that contribute to improve, maintain and help him care for his health (13)(14) ;…”
Section: Introductionmentioning
confidence: 99%